Autoimmune hemolytic anemia in children - Dinesh Chandra; Varun Capoor; Ayoniza Maitri; Rahul Naithani (Pediatric Hematology Oncology Journal, 2024)
Autoimmune hemolytic anaemia (AIHA) is an uncommon cause of antibody-induced hemolytic anemia in children. It is divided into three categories: warm AIHA, cold antibody AIHA and paroxysmal cold hemoglobinuria. The diagnostic work-up typically begins with a peripheral smear and a direct antiglobulin test. Further diagnostic approaches and pathogenesis of all three entities are discussed. Clinical trials are lacking for AIHA in children. First-line therapy for warm AIHA is corticosteroids and for cold antibody AIHA is rituximab. Data on other therapeutic agents is reviewed. Supportive care is an important aspect, particularly in cold AIHA and paroxysmal cold hemoglobinuria. Issues related to blood transfusion due to antibodies including the least incompatible blood are discussed. Tables and figures provide an overview of pathology, diagnosis and diagnostic algorithm.